2015
DOI: 10.1051/0004-6361/201525924
|View full text |Cite
|
Sign up to set email alerts
|

Abundance patterns in early-type galaxies: is there a “knee” in the [Fe/H] vs. [α/Fe] relation?

Abstract: Early-type galaxies (ETGs) are known to be enhanced in α elements, in accordance with their old ages and short formation timescales. In this contribution we aim to resolve the enrichment histories of ETGs. This means we study the abundance of Fe ([Fe/H] We then analyze a spectroscopic sample of 2286 early-type galaxies from the SDSS selected to be ETGs. We separate out those galaxies for which the abundance of iron in stars grows throughout the lifetime of the galaxy, i.e. in which [Fe/H] o < [Fe/H] i . We cal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 120 publications
(180 reference statements)
5
45
0
Order By: Relevance
“…2 we show the complete kinematics maps, produced by the software PyParadise (Husemann et al 2016, Husemann et al in prep. ), which is an improved version of Paradise (Walcher et al 2015). The left panel of Fig.…”
Section: Velocities and Velocity Mapsmentioning
confidence: 99%
“…2 we show the complete kinematics maps, produced by the software PyParadise (Husemann et al 2016, Husemann et al in prep. ), which is an improved version of Paradise (Walcher et al 2015). The left panel of Fig.…”
Section: Velocities and Velocity Mapsmentioning
confidence: 99%
“…We then estimated the velocities for each bin by fitting model template spectra from the full INDO-US template library (Valdes et al 2004) to the observed spectra using the code PyParadise (Husemann et al 2016) which is an extended Python version of paradise (Walcher et al 2015). We refer the reader to these references for the details of the algorithm.…”
Section: Velocity Dispersion Measurementmentioning
confidence: 99%
“…These methods can provide constraints on different physical properties, either exploiting a pixel-by-pixel fit to the spectrum (e.g. Cappellari & Emsellem 2004;Cid Fernandes et al 2005a;Ocvirk et al 2006;Walcher et al 2015) or interpreting single or few spectral features, for instance the emission line luminosity (Kennicutt 1998), emission line ratios (Kobulnicky & Kewley 2004), Lick absorption indices (Gallazzi et al 2005) or the 4000Å break (Bruzual A. 1983).…”
Section: Introductionmentioning
confidence: 99%